The last straw - Kinney, Jeff (New York Amulet Books, 2009)
Middle-schooler Greg Heffley nimbly sidesteps his father's attempts to change Greg's wimpy ways until his father threatens to send him to military school.
Booklist
Publishers Weekly
School Library Journal
5.4.
4-7.
970
Keywords: Middle schools -- Fiction; School stories; Family life -- Fiction; Diaries -- Fiction; Humorous fiction; Humorous fiction; Domestic fiction; Diary fiction